Substrate Pathways and Mechanisms of Inhibition in the Sulfur Oxygenase Reductase of Acidianus Ambivalens - Veith, Andreas; Urich, Tim; Seyfarth, Kerstin; Protze, Jonas; Frazão, Carlos; Kletzin, Arnulf (Frontiers in Microbiology, 2011)
Background: The sulfur oxygenase reductase (SOR) is the initial enzyme of the sulfur oxidation pathway in the thermoacidophilic Archaeon Acidianus ambivalens. The SOR catalyzes an oxygen-dependent sulfur disproportionation to H2S, sulfite and thiosulfate. The spherical, hollow, cytoplasmic enzyme is composed of 24 identical subunits with an active site pocket each comprising a mononuclear non-heme iron site and a cysteine persulfide. Substrate access and product exit occur via apolar chimney-like protrusions at the four-fold symmetry axes, via narrow polar pores at the three-fold symmetry axes and via narrow apolar pores within in each subunit. In order to investigate the function of the pores we performed site-directed mutagenesis and inhibitor studies. Results: Truncation of the chimney-like protrusions resulted in an up to seven-fold increase in specific enzyme activity compared to the wild type. Replacement of the salt bridge-forming Arg99 residue by Ala at the three-fold symmetry axes doubled the activity and introduced a bias towards reduced reaction products. Replacement of Met296 and Met297, which form the active site pore, lowered the specific activities by 25-55 % with the exception of an M296V mutant. X-ray crystallography of SOR wild type crystals soaked with inhibitors showed that Hg2+ and iodoacetamide bind to cysteines within the active site, whereas Zn2+ binds to a histidine in a side channel of the enzyme. The Zn2+ inhibition was partially alleviated by mutation of the His residue. Conclusions: The expansion of the pores in the outer shell led to an increased enzyme activity while the integrity of the active site pore seems to be important. Hg2+ and iodoacetamide block cysteines in the active site pocket, while Zn2+ interferes over a distance, possibly by restriction of protein flexibility or substrate access or product exit.